Educational Case: Lupus Nephritis as an Example of Immune Complex–Mediated Glomerulonephritis. (19th March 2020) - Jebakumar, Deborah; Jones, Kathleen A.
The following fictional case is intended as a learning tool within the Pathology Competencies for Medical Education (PCME), a set of national standards for teaching pathology. These are divided into three basic competencies: Disease Mechanisms and Processes, Organ System Pathology, and Diagnostic Medicine and Therapeutic Pathology. For additional information, and a full list of learning objectives for all three competencies, see http://journals.sagepub.com/doi/10.1177/2374289517715040 . 1